Consumer over-indebtedness: mapping the knowledge domain through bibliometrics - Lungile Ntsalaze; Tamisai Chipunza (Cogent Business & Management)
This study conducted a bibliometric analysis and literature review of consumer over-indebtedness based on research published until May 2024. The research utilised 266 publications downloaded from the Scopus database for the period 1990 to 2024. Using VOSviewer, bibliographic coupling of sources and countries, and keyword co-occurrence analysis were undertaken to show the knowledge map of consumer over-indebtedness. Co-word analysis was also performed to identify the main themes/research domains investigated over the years. Four domains were established: (1) responsible lending and borrowing, (2) consequences of over-indebtedness, (3) microfinance-driven over-indebtedness, and (4) household characteristics and over-indebtedness. Future research agenda includes evaluating the regulatory framework effective in curbing the growth of microfinance-driven over-indebtedness and investigating the nexus between macroeconomic variables and consumer over-indebtedness based on time series and panel data.